Investigation of the H(2) Oxidation System in Rhizobium japonicum 122 DES Nodule Bacteroids - Emerich, David W. (1980)
The H(2)-oxidizing complex in Rhizobium japonicum 122 DES bacteroids failed to catalyze, at a measurable rate, (2)H(1)H exchange from a mixture of (2)H(2) and (1)H(2) in presence of (2)H(2)O and (1)H(2)O, providing no evidence for reversibility of the hydrogenase reaction in vivo. In the H(2) oxidation reaction, there was no significant discrimination between (2)H(2) and (1)H(2), indicating that the initial H(2)-activation step in the over-all H(2) oxidation reaction is not rate-limiting. By use of improved methods, an apparent K(m) for H(2) of 0.05 micromolar was determined. The H(2) oxidation reaction in bacteroids was strongly inhibited by cyanide (88% at 0.05 millimolar), theonyltrifluoroacetone, and other metal-complexing agents. Carbonyl cyanide m-chlorophenylhydrazone at 0.005 millimolar and 2,4-dinitrophenol at 0.5 millimolar inhibited H(2) oxidation and stimulated O(2) uptake. This and other evidence suggest the involvement of cytochromes and nonheme iron proteins in the pathway of electron transport from H(2) to O(2). Partial pressures of H(2) at 0.03 atmosphere and below had a pronounced inhibitory effect on endogenous respiration by bacteroid suspensions. The inhibition of CO(2) evolution by low partial pressures of H(2) suggests that H(2) utilization may result in conservation of oxidizable substrates and benefits the symbiosis under physiological conditions. Succinate, acetate, and formate at concentrations of 50 millimolar inhibited rates of H(2) uptake by 8, 29, and 25%, respectively. The inhibition by succinate was noncompetitive and that by acetate and formate was uncompetitive. A concentration of 11.6 millimolar CO(2) (initial concentration) in solution inhibited H(2) uptake by bacteroid suspensions by 18%. Further research is necessary to establish the significance of the inhibition of H(2) uptake by succinate, acetate, formate, and CO(2) in the metabolism of the H(2)-uptake-positive strains of Rhizobium.